Upaya Guru dalam Membentuk Profil Pelajar Pancasila Siswa Kelas I dan IV di SDN Tanjung Duren Selatan 01 - Natasya Tambunan; Nurul Febrianti (Journal on Education, 2023)
This study aims to determine the teacher's efforts in forming Pancasila Student Profiles for students in grades I and IV at SDN Tanjung Duren Selatan 01, and to find out what factors inhibited teachers during the process of forming Pancasila Student Profiles. The research method used is descriptive qualitative. Data collection techniques used are observation, interviews and documentation. The research results obtained are: (1) Faith, piety to God Almighty and noble character. Carrying out the habit of praying Dhuha, morning services according to the elements of religious morality and morality to humans. (2) Global Diversity, by introducing ethnicity and culture in Indonesia according to elements of knowing and respecting culture and communication and interaction between cultures and social justice. (3) Work together, by picketing classes according to the moral elements of nature, collaborating, caring and sharing. (4) Independent, activities carried out by giving individual assignments according to self-regulation elements. (5) Critical Reasoning, by providing challenging questions or questions with the aim of students participating in their activities according to the elements of obtaining and processing information and ideas, and analyzing and evaluating reasoning and procedures. (6) Creative, activities carried out by giving students handicraft assignments by utilizing used items around them and holding P5 activities according to the elements of Generating original ideas and Producing original works and actions.